Inhibition of nitric oxide synthesis enhances leukocyte rolling and adhesion in human microvasculature - Hossain Mokarram; Qadri Syed M; Liu Lixin (BMC, 2012)
Abstract Background Nitric oxide (NO) is a multifunctional signaling molecule that regulates important cellular events in inflammation including leukocyte recruitment. Previous studies have shown that pharmacological inhibition of NO synthesis induces leukocyte recruitment in various in vitro and animal models. However, it is not known whether NO modulation has similar effects on leukocyte-endothelial cell interactions within the human microvasculature. The present study explored the effect of systemic L-NAME treatment on leukocyte recruitment in the SCID-hu mouse model. Methods Human skin xenografts were transplanted in SCID mice to study human leukocyte dynamics in human vasculature. Early events of human leukocyte recruitment in human vasculature were studied using intravital microscopy. NO synthesis was pharmacologically inhibited using NG-nitro-L-arginine methyl ester (L-NAME). Immunohistochemical analysis was performed to elucidate E-selectin expression in human xenograft skin. Human neutrophil-endothelial cell interactions were also studied in an in vitro flow chamber assay system. P- and E-selectin expression on cultured human umbilical vein endothelial cells (HUVECs) was measured using ELISA. Platelet-activating factor (PAF) synthesis was detected using a TLC-based assay. Results L-NAME treatment significantly enhanced the rolling and adhesion of human leukocytes to the human vasculature. Functional blocking of P- and E-selectins significantly inhibited rolling but not adhesion induced by inhibition of NO synthesis. Systemic L-NAME treatment enhanced E-selectin expression in human xenograft skin. L-NAME treatment significantly enhanced P- and E-selectin expression on HUVECs. L-NAME treatment did not significantly modify neutrophil rolling or adhesion to HUVECs indicating that L-NAME−induced subtle P- and E-selectin expression was insufficient to elicit dynamic neutrophil-HUVEC interactions in vitro. Moreover, synthesis of endothelial-derived PAF was not significantly modified by L-NAME treatment. These results point to the accelerated leukocyte recruitment in human vasculature following suppression of NO synthesis, effects that are mediated by P- and E-selectins. The findings are, however, not supported by the in vitro data. Conclusion Inhibition of endogenous NO triggers early events of human leukocyte recruitment in human vasculature, involving complex cellular or molecular mechanisms in addition to P- and E-selectin-mediated leukocyte rolling.